Effects Of Metacognition And Direct Instruction On Spelling Abilities Of Pupils With Learning Disabilities In Primary Schools In Ibadan, Oyo State, Nigeria - Lazarus, Kelechi Uchemadu; Ogunsola, Gabriel Ogundiya (European Scientific Journal, ESJ, 2016)
This study investigated the effects of metacognition and direct instruction on spelling abilities of pupils with learning disabilities in Ibadan, Oyo State, Nigeria. Pre-test, post -test, control group, quasi-experimental design with 3x2x2 factorial matrix was adopted. Purposive sampling technique was used to select three public primary schools in Ibadan. Sixty primary three pupils with spelling disabilities were randomly selected from the sampled schools and randomized into metacognition, direct instruction and control group. Four instruments were utilized: Pupil Rating Scale (r = 0.76), Right Word Recognition (r=0 .91), Pupils’ English Note Book and Test of Verbal Ability (r=0.96). Those who met the inclusion criteria were treated, while those in the control group received lessons in spelling instruction using the conventional method. Six hypotheses were tested at 0.05 level of significance. Data were analyzed using Analysis of Covariance. Despite the fact that there was no significant main effect of the treatment, participants who were exposed to direct instruction had the highest mean score of ( x = 46.35), this was followed by metacognition ( x = 44.90) while the control group obtained ( x = 30.93). There was no significant gender difference as male and female participants benefited equally from the treatment packages. Based on these findings, recommendations were made which included that teachers of pupils with learning disabilities should adopt the two strategies in teaching spelling to pupils with learning disabilities because these strategies proved better than the conventional method.